Disability awareness of frontline staff in selected hotels in the Cape Winelands - Swanepoel, Lizinda (Cape Peninsula University of Technology, 2020)
Universal Accessibility implies that everybody has an equal chance to access anything they desire; which should also be the situation in the tourism industry. The United Nations World Tourism Organisation has pleaded that tourism be open to all, despite any impairments. Universal Accessibility is not always available to visually-, intellectually-, mobile-, psychiatrically- and learning-impoverished persons — the People with Disabilities group — often denying them the tourist activity pleasures enjoyed by healthy persons. The obvious challenges include restriction of mobility but few facilities are visually impaired friendly, besides addressing the other impairments. The study question was to investigate whether hospitality staff are educated or trained to assist People with Disabilities to enjoy the facilities offered to paying guests fully at a place of accommodation. The South African Tourism Grading Council questioned whether accommodation establishments in this country were aware of the challenges which face People with Disabilities and the contribution to the South African gross domestic product of this niche group of travellers. They hinted People with Disabilities were at the mercy of poorly qualified hospitality staff. The study adopted a quanitative methodology, following convenience sampling framework, focussing on the Cape Winelands area of Cape Town. The study provisionally found that accommodation establishments did make some provision for mobility-impaired persons at the establishments and in the bedrooms but were tardy in public areas and sadly lacking in employing suitably qualified staff to address the needs of People with Disabilities. In addition, the study revealed that tourism educational institutions were also not addressing the needs of People with Disabilities. The study is of material importance to tourism organisations, such as Cape Town Tourism, in promoting tourism to one of the world’s major tourism destinations
Thesis (MTech (Tourism Management and Hospitality Management)--Cape Peninsula University of Technology, 2020
Keywords: Tourism --Social aspects -- South Africa -- Western Cape; People with disabilities -- Travel -- South Africa -- Western Cape; Social integration -- South Africa -- Western Cape; People with disabilities -- Services for -- South Africa -- Western Cape